Measuring the Level of Financial literacy of the financial consumer - Hayder Ali Abdullah (Technium Social Sciences Journal, 2024)
Through this research, the researcher sought to measure the level of financial literacy of the financial consumer, The research community included the branches of Al-Rafidain Bank in Karbala, while the research sample includedi Al-Rafidain Bank, Al-Abbas branch. The researcher relied in his research onp the questionnaire distributed to the financial consumers and investors of the bank, and the number of questionnaires was (250) questionnaires were distributed, and (249) were obtained, The researcher used Exel, Spss , and APSS to obtain the research results. The researcher concluded that the Iraqi financial consumer has the required financial literacy, Although it needs to develop itself in the technological aspect, the economic aspect, as well as the financial investment aspect, The researcher recommended conducting more studies and research regarding the factors affecting the financial consumer and holding educational courses and workshops to introduce financial literacy and include it in curricula and textbooks to realize its importance on the economic situation. The researcher also recommended serious efforts between financial institutions and related institutions in order to eliminate financial illiteracy and obtain A financially literate society.